Implementasi Fungsi Satuan Polisi Pamong Praja Di Kabupaten Gresik - Darmawan Darmawan* (Universitas Airlangga, 2018)
In the implementation of the Regional Government, Civil Service Police Unit (later called Satpol PP) has a trategic role related to the implementation of the obligations of regional government. Generally, Satpol PP has three function are : 1) Implementation of Public Peace and Order; 2) Enforcement of Regional Regulations; and 3) Community Protection. On the basis of the implementation of their duties, the Satpol PP has a formative foundation to establish Law Number 23 of 2014 concerning Regional Government; Government Regulation Number 16 of 2018 concerning Satpol PP; Minister of Home Affairs Regulation Number 54 of 2011 concerning Satpol PP Operating Standards, as well as regional regulations related to implementation technical tasks in each field. The implementation of duties in enforcement of regional regulations area, Satpol PP carried out activities such as first to provided guidance to the community and legal entities that violated regional regulations; second they conducted non-judicial control ; third they did enforce the law regarding the judiciary and the last are to supervise violation. Enforcing local regulations done by Satpol PP in Gresik Regency is carried out through pre-emptive, preventive, persuasive and represive approaches to the community without selective objectives with the aim of achieving the Regent’s vision and mission and to increase the locally- generated revenue.